The effectiveness of e-& mHealth interventions to promote physical activity and healthy diets in developing countries: a systematic review - Müller, A.M.; Alley, S.; Schoeppe, S.; Vandelanotte, C. (BioMed Central, 2016)
Background Promoting physical activity and healthy eating is important to combat the unprecedented rise in NCDs in many developing countries. Using modern information-and communication technologies to deliver physical activity and diet interventions is particularly promising considering the increased proliferation of such technologies in many developing countries. The objective of this systematic review is to investigate the effectiveness of e-& mHealth interventions to promote physical activity and healthy diets in developing countries.